Peningkatan Kapasitas Tenaga Pendidik dalam Mewujudkan Satuan Pendidikan Aman Bencana di SMAN 6 Yogyakarta - Dina Ruslanjari; Alinda Nisa; Diana Puspitasari; Feby Aulia Marsida; Fitria Nur Indah Djafar; Novi Mega Srianti (Jurnal Igakerta, 2024)
Schools are elements at risk for disasters because of the location in risk areas and the vulnerability factors of schools from the physical aspects such as building and structural and social aspects such as regulation, school environment, and the school community itself. Therefore, capacity building for disaster preparedness is needed to reduce the disaster's impact. This study aims to identify and analyze disaster problems in schools and increase knowledge and understanding of disasters in schools. This research was conducted using in-depth direct interviews and online Focus Group Discussions (FGD) with teachers and educators at SMAN 6 Yogyakarta. The research results are in the form of recommendations for schools, including preparation and socialization of the Disaster Preparedness Team in the future based on the reference of the SPAB (Disaster Safe Education Unit) program, improvement of existing evacuation routes to school residents, preparation and consolidation of the SPAB program ( Disaster Safe Education Unit) by the school together with the Education and Culture Office and the local BPBD, and the preparation of school SOPs in an emergency.